Viet Nam's water paradox - Griffiths, Steven; Gill, Ian (Information Office, Asian Development Bank, 1996)
Vietnam suffers from floods which devastate the countryside, and water shortages in its cities due to an antiquated water distribution system. This video shows how current development projects are working to solve this water paradox.